Use of scratch tracking method to study the dissolution of alpine aggregates subject to alkali silica reaction - Bagheri, Mahsa; Lothenbach, Barbara; Shakoorioskooie, Mahdieh; Leemann, Andreas; Scrivener, Karen (Cement & concrete composites, 2021)
Alkali silica reaction (ASR) can significantly affect the service life of concrete. The dissolution of aggregates has a direct impact on gel formation and thus on the macroscopic expansion. The conventional expansion tests and other investigations confirmed ASR reactivity of three aggregates from different locations in Switzerland. The reactive minerals within alpine and composite aggregates were identified using an innovative scratch-tracking method. This method helps to study aggregate dissolution if measuring the amount of released Si is not enough, because: several minerals release Si or Al and/or new phases are probable to form during dissolution experiment. The scratch-tracking method on theses alpine aggregates showed faster dissolution of feldspars and quartz while muscovite was hardly affected. The dissolution of the aggregates in solution confirmed these differences between minerals.